Mapping the Leading Potential Based on Multiple Intelligences in Early Children Education - Kurniasih Santi (Early Childhood Education & Parenting, 2024)
Children, aged 0-8, possess remarkable intelligence and talent, yet these often go unrecognised, limiting their potential for success. Parents and teachers, who are primary observers of children, sometimes overlook these abilities, hindering their expected development. Educators must prioritise understanding children's development to uncover their hidden talents and potential. By doing so, educators can guide children towards realising their full potential, leading to a brighter future. This study focuses on identifying superior potential through multiple intelligences mapping in early childhood, conducted at RA Bani Malik, Ledug. Utilising qualitative field research, data is collected through observation, interviews, and documentation. The findings reveal that each child has unique potentials, which can be identified and stimulated through various activities such as puzzle-solving for logical-mathematical intelligence, writing letters for language intelligence, dancing for musical intelligence, gymnastics for kinesthetic intelligence, caring for plants for naturalist intelligence, self-questioning activities for intrapersonal intelligence, role-playing for interpersonal intelligence, and painting for spatial intelligence.